Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

# Math: Algebra?

2x^4-16x^2-2=0

### 5 Answers

Relevance
• Favorite Answer

2x⁴ - 16x² - 2 = 0

2.(x⁴ - 8x² - 1) = 0

x⁴ - 8x² - 1 = 0

x⁴ - 8x² = 1

x⁴ - 8x² + 16 = 1 + 16

(x² - 4)² = 17

x² - 4 = ± √17

x² = 4 ± √17 → a square cannot be negative

x² = 4 + √17

x = ± √(4 + √17)

• First, remove the common factors

==> x^4 - 8x^2 - 1= 0

If you look closely at this, you will see that it could be considered a quadratic equation using x^2 and the base, rather than just x

so, substitute u for x^2

==> u^2 - 8u - 1 = 0

now solve for u

u = (8 +/- sqrt(64 + 4)/2

==> u = (8 +/- sqrt(68)/2

==> u = 4 + sqrt(17) or 4 - sqrt(17)

x = sqrt(u)

==> x = +/- sqrt(4 + sqrt(17)) or +/- sqrt(4 - sqrt(17))

Note that sqrt(4 -sqrt(17)) is a complex number (sqrt(17)> 4)

so +/- sqrt(sqrt(17)-4)i where i = sqrt(-1)

• 2x^4 - 16x^2 - 2 = 0

2 (x^2 - 4)^2 - 34 = 0

Real solutions:

x = -sqrt(4 + sqrt(17))

x = sqrt(4 + sqrt(17))

Complex solutions:

x = -i sqrt(sqrt(17) - 4)

x = i sqrt(sqrt(17) - 4)

• Presuming you want to solve for x:

2x⁴ - 16x² - 2 = 0

If we make this substitution:

z = x²

we get:

2z² - 16z - 2 = 0

We now have a quadratic that we can solve.  Let's simplify this by dividing both sides by 2, then I'll complete the square:

z² - 8z - 1 = 0

z² - 8z = 1

z² - 8z + 16 = 1 + 16

(z - 4)² = 17

z - 4 = ± √17

z = 4 ± √17

Now we can substitute back the expression in terms of x and solve for x:

x² = 4 ± √17

x = ± √(4 ± √17)

So we have four total roots.  Two of them are complex as 4 - √17 is negative.  The other two are real.

• How do you think about the answers? You can sign in to vote the answer.
• what is the question?

Still have questions? Get your answers by asking now.